ANALISIS PERENCANAAN PENGADAAN OBAT DENGAN METODE KOMBINASI ABC-VEN DI GUDANG FARMASI PUSKESMAS X KABUPATEN BANYUASIN PERIODE 2022 - Mayaranti Wilsya; Achmad Wahyudi; Sunitha Mardha Lingga; Yunilda Rosa; Khairunnisa; Sigit Cahyo Hardiansyah; Enny Octaviana (Jurnal Farmasi IKIFA, 2025)
Drug procurement planning significantly impacts the quality of pharmaceutical services in Public Health Centres (PHC). Therefore, it's crucial to ensure proper planning to avoid stockpiling of unnecessary drugs and shortages of vital medications, which can ultimately decrease the quality of care. This study investigates the use of the ABC-VEN analysis method to optimize drug procurement planning within budget constraints at PHC X. Employing a descriptive, non-experimental design with retrospective data, the study analyzed drug demand data from January to December 2022. Primary data was collected through in-depth interviews with informants regarding the drug procurement planning process. The ABC-VEN analysis conducted for the period January-December 2022 categorized the drugs as follows: DAK drugs - 22 items (Priority), 87 items (Main), and 8 items (Additional); DPR drugs - 7 items (Main) and 2 items (Additional); JKN drugs - 10 items (Main) and 1 item (Additional). Based on the ABC-VEN analysis of drug procurement planning at PHC X for the January-December 2022 period, a total of 137 drug items were planned by the pharmacy warehouse. These were categorized as: 22 items in Group P (Priority), 104 items in Group U (Main), and 11 items in Group T (Additional).